2017
DOI: 10.1038/s41598-017-03744-3
|View full text |Cite
|
Sign up to set email alerts
|

SerpinB3 Promotes Pro-fibrogenic Responses in Activated Hepatic Stellate Cells

Abstract: SerpinB3 is a hypoxia- and hypoxia-inducible factor-2α-dependent cystein protease inhibitor that is up-regulated in hepatocellular carcinoma and in parenchymal cells during chronic liver diseases (CLD). SerpinB3 up-regulation in CLD patients has been reported to correlate with the extent of liver fibrosis and the production of transforming growth factor-β1, but the actual role of SerpinB3 in hepatic fibrogenesis is still poorly characterized. In the present study we analyzed the pro-fibrogenic action of Serpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…The involvement of HRGP in mediating the effects of HIF‐2α activation during NAFLD progression does not rule out the possible involvement of other mediators. We previously reported that HIF‐2α activation in human liver cancer cells up‐regulates Serpin B3 and that this contributes to the development of fibrosis during CLD by sustaining the most relevant profibrogenic responses by activated stellate cells . Unfortunately, unlike in humans, SerpinB3 is virtually undetectable in murine livers during CLD; thus, in the present study we did not have the chance to evaluate its contribution to NAFLD progression.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The involvement of HRGP in mediating the effects of HIF‐2α activation during NAFLD progression does not rule out the possible involvement of other mediators. We previously reported that HIF‐2α activation in human liver cancer cells up‐regulates Serpin B3 and that this contributes to the development of fibrosis during CLD by sustaining the most relevant profibrogenic responses by activated stellate cells . Unfortunately, unlike in humans, SerpinB3 is virtually undetectable in murine livers during CLD; thus, in the present study we did not have the chance to evaluate its contribution to NAFLD progression.…”
Section: Discussionmentioning
confidence: 82%
“…In vitro experiments in this study were performed in normal HepG2 cells (American Type Culture Collection) as well as in cells stably transfected in order to overexpress HIF‐2α in either normoxic or hypoxic conditions, as reported . Western blot analysis was performed on total cell or tissue lysates as described . More details on in vitro studies and western blot analysis are available in the http://onlinelibrary.wiley.com/doi/10.1002/hep.29754/suppinfo.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, levels of circulating SCCA-IgM have been recently found to increase over time, being predictive of fibrosis progression in patients with chronic hepatitis [47] . Furthermore, it has been demonstrated that HCV-infected cirrhotic patients with low levels of serum SCCA-IgM have a decreased risk of developing HCC [48] .…”
Section: Serpinb3mentioning
confidence: 99%